Effectiveness of Developing the Technique of Attacking Movements of Young Volleyball Players - Umarov, K. M.; Sultanov, R. T.; Baxtiyorova, M. B. (Pubmedia Jurnal Pendidikan Olahraga, 2024)
In this article, the process of development of attacking techniques of 13-14-year-old volleyball players is studied. During the research, a set of exercises aimed at increasing the efficiency of the participants' attack techniques was developed and these exercises were used by the participants of the experimental group. The developed set of exercises had a positive effect on the effectiveness of the offensive movements of the participants in the experimental group. In particular, the quality of attack movements, and the accuracy and efficiency of shots achieved positive growth in the experimental group. The results of the research serve to improve the technical and tactical training of young volleyball players and to organize training effectively.